Analyzing The Militarization Of Ladakh And Mapping Its Environmental Implications For The Region (International Journal of Environmental Sciences, 2025)
Since Xi Jinping became the president of the People's Republic of China (PRC), India-China relations have incrementally developed an increasing perception of distrust. This perception has notably risen due to the militarization of the India-China border in Western Ladakh. Using discourse and development in Chinese official documents, Chinese leaders’ speeches, and media in addition to the material developments in the border, particularly in the context of the militarization in Western Ladakh, the article analyses China’s militarization process in the Western Himalayan region. The article argues that the accelerated militarization of the India-China border in Western Ladakh has implications for the region’s environmental security.